Toward a Safer and Cleaner Way: Dealing With Human Waste in Healthcare. (July 2016) - Apple, Michael
Organizations must evaluate their infection control plans in a holistic and inclusive manner to continue reducing healthcare-associated infection (HAI) rates, including giving consideration to the manner of collecting and disposing of patient waste. Manual washing of bedpans and other containers poses a risk of spreading infection via caregivers, the environment, and the still-contaminated bedpan. Several alternative disposal methods are available and have been tested in some countries for decades, including options such as bedpan washer–disinfector machines, macerator machines, and disposable bedpans. This article reviews methods and issues related to human waste disposal in healthcare settings. Healthcare organizations must evaluate the options thoroughly and then consistently implement the option most in line with its goals and culture.